Comparative analysis of motive activity with a ball and without in training of different playing lines of young footballers aged 11-15 years - Y.O. Usakovsky; N.I. Bova (Physical Education of Students)
Motive activity of young footballers of different playing lines of business is considered. For research is served the actions of players aged 11-15 years (n=93). The analysis of motive activity of footballers is presented with ball and without on the stage of base pre-treatment. The value of motive activity is appraised for competition activity of footballers. The necessity of development of specific capacity of footballers is certain. It is set that dimension of motive activity of 11 years footballers (20 persons) includes slow runs - from 23,9 to 25 minutes; accelerations on different distances - from 3 to 3,4 minute; jerks - from 2 to 3,4 minute; jumps and fight for a ball - from 0,9 to 1,1 minute. On the average for training (90 minutes) footballers running during 45 minutes (from them 4 minutes of contiguities with ball).